Developing countries in the GATT legal system / Robert E. Hudec ; with an introduction by J. Michael Finger. - Hudec, Robert E. (Cambridge University Press, 2011)
In this reissued edition of the classic work Developing Countries in the GATT Legal System, Robert E. Hudec's clear insight on the situation of developing countries within the international trade system is once again made available. Hudec is regarded as one of the most prominent commentators on the evolution of the current international trade regime, and this long out-of-print book offers his analysis of the dynamics playing out between developed and developing nations. A significant contribution when the book was first published, this work continues to serve as a thoughtful and important guide to how current and future trade policy must seriously adapt to the demands of the developing world. This new edition includes a new introduction by J. Michael Finger that examines Hudec's work to understand how the GATT got into its current historical-institutional predicament and the lasting impact of his work on current research on international trade systems.